Sketching light : an illustrated tour of the possibilities of flash - McNally, Joe , 1952- (New Riders, 2012)
Following "The Moment It Clicks" and "The Hot Shoe Diaries: Big Light from Small Flashes," legendary magazine photographer McNally takes readers on another trip into the land of light--but this time running the gamut from small flash to big flash, and everywhere in between